New attractants for Vespula vulgaris from honeydew - White, N.J.; Gibb, A.R.; Stringer, L.D.; Manning, L.M.; Unelius, C.R.; Park, K.C.; Suckling, D.M.; El-Sayed, A.M. (New Zealand Plant Protection, 2008)
The common wasp (Vespula vulgaris) is a major pest species in New Zealands forests and urban areas Attractants for wasps could enable new environmentallyfriendly management techniques against this invasive species Beech forest honeydew known to be attractive to vespid wasps was analysed using Solid Phase Micro Extraction Several volatile compounds were identified and two compounds (I and II) were tested for attraction in a Canterbury beech forest Four different lures (manuka honey; compound I; compound II; and a blend of compounds I and II) were placed in delta traps and the number of V vulgaris trapped recorded Compound II trapped significantly more V vulgaris than manuka honey and compound I and had significantly less honey bee (Apis mellifera) bycatch than the other three lures A controlled release experiment was carried out by placing 05 ml of compound II in vials with a 2 4 or 6 mm diameter hole or no hole in the lid The 4 mm treatment caught significantly more V vulgaris than the control no hole and 2 mm treatments A gravimetric release rate experiment on compound II in the laboratory showed a significant difference in weight loss between treatments These results suggest that compound II deserves further research as a wasp attractant